Reading comprehension problems in Chinese among children in a Malaysian international school - Zhong, Kai; Wong, Ling Yann; Yong, Mei Fung; Ng, Boon Sim (Human Resource Management Academic Research Society, 2024)
While extensive research has explored student’s problems in reading comprehension, studies specifically examining the problems faced by child learners of Chinese as a Foreign Language (CFL) in reading comprehension have been relatively scarce. This research aimed to examine reading comprehension problems in CFL children at an international school in Malaysia. Forty-four child learners of CFL were evaluated on their knowledge in character, morpheme, vocabulary, grammar, and passage reading comprehension abilities. Through descriptive and error analysis, this study revealed several key issues: participants failed to identify the target characters even when contextual clues were provided, overgeneralized character knowledge, were unfamiliar with extended morpheme meanings, incorrectly discriminated between morphemes based on their position in vocabulary, mistreated disyllables with similar structures as synonyms, struggled to order sentences in serial verb constructions (SVS), and made more errors on implicit than explicit questions in the passage reading. The conclusions of the study are presented along with implications for pedagogy and suggestions for further research.